2022
DOI: 10.1021/acs.analchem.2c01688
|View full text |Cite
|
Sign up to set email alerts
|

Single Fluorescent Probe for Zero-Crosstalk Discrimination of Lipid Droplets and the Endoplasmic Reticulum Based on Reversible Cyclization Reaction

Abstract: The interactions between different organelles are ubiquitous and crucial for life activities. Thus, development of a single fluorescent probe enabling the simultaneous two-color visualization of two organelles is of great significance for the study of organelle interplay. Herein, using the reversible ringopening/closing reactions of rhodamine dyes, we have fabricated a robust fluorescent probe to distinguish lipid droplets (LDs) and the endoplasmic reticulum (ER) in dual-emission channels with negligible cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…LDs are highly dynamic organelles and closely related to other organelles, such as lysosomes. Lipophagy is an important physiological process by which disabled LDs are swallowed by lysosomes to maintain the cytoplasmic environment, and it has been reported that lipophagy is closely connected with many diseases. ,, Inspired by the superior biocompatibility, favorable photostability, and good LD specificity of the probe, AIE-Cbz-LD-C 7 was used to track the dynamic LD behaviors during lipophagy induced by starvation in living HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LDs are highly dynamic organelles and closely related to other organelles, such as lysosomes. Lipophagy is an important physiological process by which disabled LDs are swallowed by lysosomes to maintain the cytoplasmic environment, and it has been reported that lipophagy is closely connected with many diseases. ,, Inspired by the superior biocompatibility, favorable photostability, and good LD specificity of the probe, AIE-Cbz-LD-C 7 was used to track the dynamic LD behaviors during lipophagy induced by starvation in living HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular organelles have distinct essential functions, and understanding each organelle and its contribution to disease pathophysiology has been a topic of intensive research in recent years. , Currently, some studies have found multiple functional interactions between the organelles that have played a cooperative role in many cellular physiological and pathological processes. , Lipid droplets (LDs), which consist of a phospholipid monomembrane and a neutral core containing metabolic lipids, play a significant role in many physiological processes including protein storage, cell metabolism, and proliferation. In recent studies, LDs were found to be related to numerous pathological processes such as neurodegeneration, fatty liver diseases, atherosclerosis, diabetes, and even cancers. Additionally, because LDs are highly dynamic organelles, they have been suggested to have close connections with other organelles like mitochondria, lysosomes, and endoplasmic reticulum (ER). Previous studies of LDs have mainly focused on their dynamic behaviors and relationship to the tumorigenesis. The mutual cooperation and close association between LDs and other organelles during some physiological processes are rarely reported. Therefore, it is very important to develop a dynamic monitoring tool for directly visualizing and studying the interplay between LDs and other organelles.…”
mentioning
confidence: 99%
“…The use of molecules with differing partitioning behaviors and fluorescence properties also enables multiple structures to be tracked over time with minimal photodamage. Properly designed probes can report multiple attributes of the microenvironment including membrane fluidity, local polarity, lipid composition, domain sizes, and temporal properties (145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)160). Newer probes such as PIE-1 possess high fluorescence quantum yield and photostability, further improving upon measurement attributes for live cell imaging including imaging speed (147).…”
Section: Fluorescence Microscopymentioning
confidence: 99%
“…The rhodamine derivative used as a uorophore for this probe has many merits of high quantum yield, great water-solubility, and a long emission. [39][40][41][42] Importantly, the positive charge carried by this uorophore endows it with the ability to target mitochondria. The additionally attached allyl moiety serves as the reaction site, and in response, the hydroxyl group is exposed, releasing a uorophore with a strong ICT structure, and the red strong uorescence is restored.…”
Section: Introductionmentioning
confidence: 99%